Steatitis in a Wild Common Loon (Gavia immer) and Review of the Literature - Bridgers, Jessica; Hall, Sara; Lawrence, Yuri; Rittle, Tara; Harris, Becky; Pokras, Mark (Wildlife Rehabilitation Bulletin, 2012)
Steatitis was diagnosed at necropsy in a debilitated, adult female common loon (Gavia immer), constituting the first known case of the disease in loons. Steatitis has been described most commonly in a variety of domestic and captive species. In these cases, the cause of steatitis is most often vitamin E deficiency in a diet comprised mainly of fish. Until roughly 20 years ago, the occurrence of steatitis in wildlife was relatively rare. However, the condition is being seen increasingly in herons in Japan and both coasts of the US. While several environmental factors have been correlated with the outbreaks, the causes remain unclear and may be multifactorial. Rehabilitators are in a unique position to recognize and report the event of steatitis in wild birds such as loons, allowing researchers to better understand the extent and cause of steatitis in wild birds.